Characteristic of black soy miso with crude bromelain and Lactobacillus plantarum - Bhakti Etza Setiani; Yoyok Budi Pramono; Nurwantoro Nurwantoro; Bambang Dwiloka; Annisa Shafa Putri Arini; Ilma Muliasari Ramadhaningrum; Elisabeth Febriane Lovita Sudjono (Institute of Advanced Engineering and Science, 2024)
This research aims to improve the diversity of functional foods rich in bioactive peptide components and have a unique flavor for black soybean miso through the addition of crude bromelain and Lactobacillus plantarum. This research uses a completely randomized design with 5 treatments and 4 repetitions to obtain a total of 20 experimental units. The treatments are the different concentrations of crude bromelain addition, namely the control treatment or 0% (T0), 3% (T1), 6% (T2), 9% (T3), and 12 % (T4). The parameters observed are water content, water activity, pH value, and lactic acid bacteria (LAB) viability. The result showed that an increase in the crude bromelain concentration may increase the water content and water activity of the black soybean miso, while the pH value decreases. Based on the viability of the LAB showed a wavering result. Miso with the 9% concentration of crude bromelain is the best result among the others.